Oskar Pfister e a crítica à concepção freudiana de Religião - Veliq, Fabiano (2017)
The criticism that Freud makes to religion permeates all his work so that we can say that the religious question shown a big issue for him. However, it is clear that the vision that Freud has of religion is rather reductive and it is quite clear in many texts of this author. Oskar Pfister stands as a great debater of the religious question at the beginning of psychoanalytic movement showing the various gaps in Freud's view of religion. This article aims to explain the criticism made by Pfister to Freud's conception of religion in order to bring this element to the debate between psychoanalysis and religion.